The Utilization of Zakah Productive towards Micro-Business Growth and Mustahik Welfare - Muhammad Irfan Nasution; Muhammad Andi Prayogi (Muhammadiyah University Press, 2019)
One of the basic laws that the zakat seems to be ordered is the word of Allah SWT QS. At-Taubah verse 103, The study aims to analyze the effect of productive Zakat, Infak, Sedekah (ZIS) to the micro-business growth of mustahik of Muhammadiyah Society in Medan City, micro-business growth towards mustahik welfare of Muhammadiyah Society in Medan City, and simultaneously effect of Productive Zakat, Infak, Sedekah (ZIS) and micro-business growth to the mustahik welfare of Muhammadiyah society in Medan City. This research used quantitative descriptive analysis, the sample was selected by using quota sampling, and the data analysis technique used was multiple linear regression analysis. The results showed that there is a positive and significant influence between productive Zakat and mustahik welfare, there is a relationship between micro-business growth and mustahik welfare and also simultaneously there is a relationship between productive Zakat and the micro-business growth towards mustahik welfare of Muhammadiyah society in Medan city. The implication of this study is emphasizing the distribution of Zakat that more prioritizing on Productive Zakat.